My life in recipes : food, family, and memories - Nathan, Joan (Alfred A. Knopf, 2024)
"A memoir-in-recipes from the best-selling and award-winning author that looks back at her family and at the long century of Jewish cooking in Europe and America. In her most personal book, Joan Nathan looks back at her own family's history - her family's arrival in America from Germany, Poland, and Slovakia; her childhood in post-war New York and Rhode Island; the influence of her in-laws, who came from Poland after fleeing the Nazis; her years in New York, Israel, and Washington, DC. Nathan shares her story - a life well-lived and centered around meals - and she punctuates it with all the recipes she has come to love. From roast chicken to rugelach, from matzoh ball soup to challah and brisket, here are updated versions of her most beloved recipes. But here too are new favorites: Fragrant Spiced Chicken with Rice, Eggplant, Peppers and Zucchini, Yemeni White Bean Stew, and a Pecan Lemon Torte. This is a treasury of recipes and stories - and an invitation to a seat at Joan's table"--